2015
DOI: 10.1016/j.envint.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to phthalates, bisphenol A and metals in pregnancy and the association with impaired glucose tolerance and gestational diabetes mellitus: The MIREC study

Abstract: Our findings add to the growing body of evidence supporting the role of maternal arsenic exposure as a risk factor for gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(121 citation statements)
references
References 73 publications
4
110
4
1
Order By: Relevance
“…These results were similar to our observation of an association between toenail As and GDM. In a large longitudinal study of 1274 Canadian women, Shapiro et al observed a positive relationship between the highest quartile of first trimester blood As and GDM (OR: 3.7, 95 % CI: 1.4, 9.6), as well as with combined GDM and glucose intolerance (OR: 1.9, 95 % CI: 1.1, 3.5) [22]. A nested case–control study within pregnancy cohort of Chinese women compared metals, including As, in meconium samples from infants born to healthy mothers ( n  = 190) or mothers with GDM ( n  = 137).…”
Section: Discussionmentioning
confidence: 99%
“…These results were similar to our observation of an association between toenail As and GDM. In a large longitudinal study of 1274 Canadian women, Shapiro et al observed a positive relationship between the highest quartile of first trimester blood As and GDM (OR: 3.7, 95 % CI: 1.4, 9.6), as well as with combined GDM and glucose intolerance (OR: 1.9, 95 % CI: 1.1, 3.5) [22]. A nested case–control study within pregnancy cohort of Chinese women compared metals, including As, in meconium samples from infants born to healthy mothers ( n  = 190) or mothers with GDM ( n  = 137).…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with insulin resistance at second trimester (Lacroix et al 2014). Growing evidence suggests a role of environmental chemicals, as arsenic, phthalates, bisphenol A, metals NOx, SO 2, and O 3, in the development of GDM (Robledo et al 2015;Shapiro et al 2015). By contrast, moderate coff ee and tea intake may have a protective eff ect (Hinkle et al 2015).…”
Section: Risk Factorsmentioning
confidence: 99%
“…[25] However, this study only assessed the exposure to phthalates, a non-persistent chemical, at one time-point. Also, they evaluated the association between urinary phthalate metabolites and overt GDM, without assessing risk factors related to GDM or actual glucose levels to determine whether these chemicals had an effect on GDM risk factors or elevated glucose levels in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they evaluated the association between urinary phthalate metabolites and overt GDM, without assessing risk factors related to GDM or actual glucose levels to determine whether these chemicals had an effect on GDM risk factors or elevated glucose levels in pregnancy. [25] Evaluating the relationship of these risk factors with urinary phthalate metabolites is important, given that pre-pregnancy obesity confers a 2- to 3-fold increased risk of GDM, while excessive GWG in early pregnancy is associated with an ~70% increased risk of GDM. [26, 27]…”
Section: Introductionmentioning
confidence: 99%